A Review of Security Technique for Content-Based Image Retrieval in the Cloud Computing - Anitha, K; Madhura, P (International Journal of Computer Sciences and Engineering, 2025)
Content-based picture recuperation (CBIR) applications had been fast created along the enlargement in the quantity, accessibility and importance of pix in our day by day existence. Be that as it may, the huge association of CBIR conspire has been constrained with the aid of it's the extreme calculation and potential prerequisite. Content Based Image Retrieval (CBIR) is an efficient retrieval of relevant images from large databases based on features extracted from the image. This paper proposes a system that can be used for retrieving images related to a query image from a large set of distinct images. It follows an image segmentation based approach to extract the different features present in an image. The above features which can be stored in vectors called feature vectors and therefore these are compared to the feature vectors of query image and the image information is sorted in decreasing order of similarity. The processing of the same is done on cloud. The CBIR system is an application built on Windows Azure platform. It is a parallel processing problem where a large set of images have to be operated upon to rank them based on a similarity to a provided query image by the user. Numerous instances of the algorithm run on the virtual machines provided in the Microsoft data centers, which run Windows Azure. Windows Azure is the operating system for the cloud by Microsoft Incorporation.